2020
DOI: 10.1057/s41599-020-00545-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of monthly economic losses in Wuhan under the lockdown against COVID-19

Abstract: With the outbreak of COVID-19 in Wuhan, aggressive countermeasures have been taken, including the implementation of the unprecedented lockdown of the city, which will necessarily cause huge economic losses for the city of Wuhan. In this paper, we attempt to uncover the interactions between epidemic prevention and control measures and economic-social development by estimating the health loss and meso-economic loss from a human-oriented perspective. We implemented a compartmental model for the transmission dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…Recently, several research studies have empirically demonstrated that economic shocks are propagating. A research by You et al [ 64 ] showed that the direct economic losses in the transportation, logistics, warehousing, postal, food, and beverage service industries of China amount to CNY 21.61 billion, and the monthly indirect economic losses are CNY 36.4 billion for all industries. During lockdown, the gross monthly economic losses hit CNY 177.04 billion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several research studies have empirically demonstrated that economic shocks are propagating. A research by You et al [ 64 ] showed that the direct economic losses in the transportation, logistics, warehousing, postal, food, and beverage service industries of China amount to CNY 21.61 billion, and the monthly indirect economic losses are CNY 36.4 billion for all industries. During lockdown, the gross monthly economic losses hit CNY 177.04 billion.…”
Section: Discussionmentioning
confidence: 99%
“…Mass testing has been mooted as the most practical and straightforward way 1,2 to curb the SARS-CoV-2 pandemic, as it allows health authorities to rapidly identify and isolate infectious individuals, thus limiting the spread of disease and minimizing the need for drastic widespread lockdown measures, which can have negative socioeconomic consequences 15 . Even in places which have successfully controlled the initial wave of SARS-CoV-2 infections, population-scale mass testing has been proven to be helpful in identifying asymptomatic cases 30,31 that have been missed by symptom-based detection regimes but could still contribute to silent transmission of the virus 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Mass testing has been proposed as a strategy to contain and break the cycle of SARS-CoV-2 transmission 1,2 while minimizing the need for drastic restrictive measures such as lockdowns, for which extended implementation is impractical due to severe, negative social and economic impacts 15 . Population-wide mass surveillance will also allow the detection of asymptomatic cases, estimated to be approximately 20% of total cases 16,17 , which form a contagious pool that contributes to viral transmission 18,19 but are difficult to identify with existing symptom-based detection protocols.…”
Section: Introductionmentioning
confidence: 99%
“…By using the models to simulate the transmission process, recent studies mainly focus on predicting propagation trends [11] , tracing transmission dynamics [12] , estimating infection risk [13] , and evaluating intervention effects [3] , [14] . Existing studies on the relation between COVID-19 and economics mainly stays in descriptive or analytical analysis [15] , [16] . Typical works include quantitatively analyzing the impact of the COVID-19 pandemic in low- and middle-income countries [15] , and evaluating the monthly economic losses in Wuhan under the lockdown against COVID-19 by using compartment model and Input–Output model [16] .…”
Section: Introductionmentioning
confidence: 99%